2015
DOI: 10.1088/0004-637x/810/2/141
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Galactic Electrons in the Heliosphere During the Unusual Solar Minimum of 2006–2009: A Modeling Approach

Abstract: The last solar minimum activity period, and the consequent minimum modulation conditions for cosmic rays, was unusual. The highest levels of Galactic protons were recorded at Earth in late 2009 in contrast to expectations. A comprehensive model was used to study the proton modulation for the period from 2006 to 2009 in order to determine what basic processes were responsible for solar modulation during this period and why it differs from proton modulation during previous solar minimum modulation periods. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(136 citation statements)
references
References 42 publications
4
131
0
Order By: Relevance
“…For both electrons and protons the newly determined local interstellar spectra, see also Potgieter et al (2014a), used as unmodulated input spectra for the model are also shown in the two figures. The different behaviour of electrons in comparison with protons at low rigidities were discussed in detail by Potgieter et al (2014bPotgieter et al ( , 2015 and is not repeated here. In the rest of our work, we focus on rigidities above 0.4 GV, which is the lowest rigidity available for the proton spectra.…”
Section: The Pamela Electron and Proton Differential Fluxesmentioning
confidence: 96%
See 2 more Smart Citations
“…For both electrons and protons the newly determined local interstellar spectra, see also Potgieter et al (2014a), used as unmodulated input spectra for the model are also shown in the two figures. The different behaviour of electrons in comparison with protons at low rigidities were discussed in detail by Potgieter et al (2014bPotgieter et al ( , 2015 and is not repeated here. In the rest of our work, we focus on rigidities above 0.4 GV, which is the lowest rigidity available for the proton spectra.…”
Section: The Pamela Electron and Proton Differential Fluxesmentioning
confidence: 96%
“…Strauss & Potgieter 2014a). This approach leads to reliable estimates for both the proton and electron LIS (see also Potgieter et al 2015;.…”
Section: Modulation Theory and Numerical Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical model used in this study is further described in detail by Potgieter et al (2014Potgieter et al ( , 2015. The modulation parameters as modeled are discussed below.…”
Section: Modeling the Pamela Proton Spectramentioning
confidence: 99%
“…Voyager 1 was assumed to have crossed the heliopause (HP) at ∼ 122 AU on August 2012 (Webber & McDonald 2013), cosmic ray spectra in the energy between 5 MeV to 50 MeV in the very local interstellar medium was then reported by Stone et al (2013). The cosmic ray spectra data from PAMELA and Voyager 1 can be used to construct the very local interstellar spectrum (LIS, see e.g., Potgieter et al 2014;Ngobeni & Potgieter 2014;Potgieter et al 2015;Bisschoff & Potgieter 2016). The LIS is important as the input spectrum in the solar modulation study.…”
Section: Introductionmentioning
confidence: 99%